Penerapan Model COBIT 5 dalam Audit Sistem Informasi Penerimaan Negara Bukan Pajak Online Pada Lembaga Penyiaran Publik Radio Republik Indonesia - Wahyudin Hasyim; Moh. Ilyas Abas; Rahmatia Mohi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Audit is an independent and standardized systematic process that completes evidence and compares it objectively to determine the extent to which audit interpretations have been complied with. One of the standards used in the implementation of the information systems audit process is COBIT (Control Objectives for Information and Related Technology). Online PNBP still has identified problems, including that the Online PNBP application does not accommodate all Types and Tariffs for PNBP types. This study aims to conduct an online PNBP information system audit at LPP RRI Gorontalo. This study uses the APO04 (Manage Innovation) domain at COBIT 5 with the research stages using Assessment Process Activities. The data used in this study are secondary data and primary data obtained through the observation phase of interviews and questionnaires. Based on the research results, the average value in the APO04 sub-domain in the current condition (As Is) is 0.24 and the expected condition (To Be) is 0.20 or still at level 0. With the largest gap or gap value is in the APO04.02 sub domain, which is 0.54. With these results it is found that LPP RRI Gorontalo has not carried out IT processes that should have existed, or been added and have not succeeded in achieving the objectives of the IT process and have not been optimal in maintaining understanding of the company's environment, so the suggestion that can be given is to maximize understanding of the environment companies so that they can understand the interests of both consumers and companies so that opportunities enabled by new technologies can be identified